Do farmer and credit specific characteristics matter in microfinance programmes' participation? Evidence from smallholder farmers in Ada west and east districts. Issue 3 (3rd June 2019) - Jumpah, Emmanuel Tetteh; Osei-Asare, Yaw; Tetteh, Emmanuel Kodjo
Abstract : Purpose: Users of smallholder farmer microfinance are able to make enough returns to repay credits advanced to them. However, they are in dire need of financial capital such that they are inconsiderate of farmer- and credit-specific characteristics when participating in a microfinance programme. This study analyses perceptions of stakeholders regarding select farmer and credit characteristics within the microfinance industry. The study identifies and analyses the factors that influence participation in a microfinance programme by farmers using the logistic regression model. The purpose of this paper is to widen the knowledge base of rural agricultural finance, including factors that influence participation in microfinance intervention(s) thereof. Design/methodology/approach: A total of 104 participants and 120 non-participant farmers in microfinance programmes were interviewed using a semi-structured questionnaire by applying the multistage sampling technique. The paper applied the logistic regression model in which farmer- and credit-specific characteristics were used to estimate the probabilities of participation. Findings: The logistic regression results showed that distance, interest rate, experience, membership of farmer-based organisation, number of dependants, household, gender and age were statistically significant farmer- and credit-specific characteristics that influence participation in microfinance programmes. Interest rate and distance exact negative significance influence on participation, whereas membership of farmer-based organisations, experience, gender, household head and age influence participation positively. Reduction in the interest rate and expansion of microfinance to very remote areas rather than locations in urban areas are crucial in terms of improving participation. Research limitations/implications: The paper used data from only farmers so there is a limit to which the results can be generalised for all microfinance users. It may be relevant to undertake a study that considers non-farm enterprises. Practical implications: This paper brings to light the need to develop well-structured microfinance facilities that meet the specific needs of the rural poor in transitioning economies while taking into consideration critical factors affecting participation before the establishment of such programmes. Originality/value: This paper provides empirical evidence to show that farmer- and credit-specific characteristics are essential to ensure participation and success of microfinance programmes thereof.